PERDAGANGAN LADA DI SUNDA ABAD XVI - Fitriansyach, Ashanty Thania; Wijaya, Daya Negri (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2024)
This article examines the pepper trade carried out by the Sunda Kingdom in the 16th century. The topic of pepper trade was chosen because pepper was one of the main commodities that played an important role in the economy and international relations of the Sunda Kingdom. The main aim of this research is to examine the role of pepper as the main commodity of the Sunda Kingdom on the social and economic relations of the Sunda Kingdom. The research method used is historical research which consists of five stages, namely topic selection, heuristics, source criticism, interpretation, and historiography. This research is intended to examine (1) the Sunda Kingdom and the pepper trade, (2) the arrival of the Portuguese in Malacca, (3) Javanese geopolitics in the 16th century, (4) the 16th century pepper trade. The Sunda Kingdom had an agricultural and maritime character, with a focus on agriculture inland and trade in coastal areas. This kingdom planted pepper in the interior, which was then distributed to the big cities owned by the Sunda Kingdom for trade. The research results indicate that the pepper produced by the Sunda Kingdom is of high quality. This attracted the attention of the Portuguese to establish diplomatic relations. However, these efforts were thwarted by strong resistance from local kingdoms, especially Demak. The strategic position of the Sunda Kingdom in the maritime trade network is reflected in its extensive economic interactions, including trade relations with China, Malacca, and others. The diversity of networks and intensity of trade emphasize the influence of pepper in determining the political and economic situation of that time.